2022
DOI: 10.1161/svin.121.000154
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Venous Stenosis as the Dominant Cause of Pulsatile Tinnitus

Abstract: BACKGROUND The role of arteriovenous shunts such as dural fistulas, arterial steno‐occlusive states, anatomic variants, and hypervascular tumors in the genesis of pulsatile tinnitus (PT) has long been recognized. On the venous side, diverticula, high‐riding jugular bulb, and sinus wall dehiscence have also been implicated. However, the overall most common cause—venous sinus stenosis (VSS)—continues to be underrecognized. Its clinical importance, separate from venous stenosis association with intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In addition, we routinely treat these patients with medical management for IIH (ie, Diamox and weight loss) for 6 months before considering venous sinus stenting, since many will have an adequate response. Our experience is comparable to a recent study by Raz et al which found venous sinus stenosis to be the most common cause of PT (34% of patients), typically diagnosed with non-invasive imaging or even solely with clinical history and physical examination 17. In these cases, endovascular evaluation may still play a vital role in planning and providing treatment for debilitating PT.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, we routinely treat these patients with medical management for IIH (ie, Diamox and weight loss) for 6 months before considering venous sinus stenting, since many will have an adequate response. Our experience is comparable to a recent study by Raz et al which found venous sinus stenosis to be the most common cause of PT (34% of patients), typically diagnosed with non-invasive imaging or even solely with clinical history and physical examination 17. In these cases, endovascular evaluation may still play a vital role in planning and providing treatment for debilitating PT.…”
Section: Discussionsupporting
confidence: 83%
“…Stenoses at transverse/sigmoid sinus junctions have been definitively linked to intracranial hypertension 32 and pulsatile tinnitus [33][34][35][36] (figure 10). The latter can be present as a sole symptom, without intracranial hypertension, or in a setting of mildly increased cerebrospinal fluid pressures, with no visual or other findings.…”
Section: Venous Sinus Stenosismentioning
confidence: 99%